2020
DOI: 10.1021/acs.biochem.0c00013
|View full text |Cite
|
Sign up to set email alerts
|

Subverting Hedgehog Protein Autoprocessing by Chemical Induction of Paracatalysis

Abstract: Hedgehog proteins, a family of vital cell signaling factors, are expressed in precursor form, which requires specialized autoprocessing, called cholesterolysis, for full biological activity. Cholesterolysis occurs in cis through the action of the precursor’s C-terminal enzymatic domain, HhC. In this work, we describe HhC activator compounds (HACs), a novel class of noncovalent modulators that induce autoprocessing infidelity, diminishing native cholesterolysis in favor of precursor autoproteolysis, an otherwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Accordingly, cholesterol ligation can occur in vitro and in cells when the Hh N-terminus is replaced by fluorescent proteins or simply by a His-tag. [18][19][20][21][22] However, the molecular details of the SRR that facilitate cholesterol transfer remain unknown. The SRR, which spans 50-100 residues in different species, bears no clear homology to known proteins in any domain of life.…”
mentioning
confidence: 99%
“…Accordingly, cholesterol ligation can occur in vitro and in cells when the Hh N-terminus is replaced by fluorescent proteins or simply by a His-tag. [18][19][20][21][22] However, the molecular details of the SRR that facilitate cholesterol transfer remain unknown. The SRR, which spans 50-100 residues in different species, bears no clear homology to known proteins in any domain of life.…”
mentioning
confidence: 99%
“…With the resulting approximation, we created a full lipid bilayer containing 100 POPC molecules in each leaflet with~20% cholesterol content (24 cholesterol molecules in each leaflet), approximating the composition of cholesterol-rich microdomains in the Golgi and endoplasmic reticulum [41][42][43][44]. Several previous studies have demonstrated that Hedge domain residues N-terminal to C198 are not required for cholesterolysis [45][46][47][48]; therefore, we modeled the N-terminal portion of hSHH (C24-G197) as a G197-C198 thioester preceded by a S195-G196 dipeptide for computational simplicity. To prepare the system for MD simulations, we solvated the protein, neutralized charges with NaCl (0.15 M), and adjusted the system to physiological pH (7.4).…”
Section: Simulations Place a Hshh Hog Protein On The Membranementioning
confidence: 99%
“…Library screening for HhC inhibitors: We tested 1187 steroid analogs from ChemBridge as potential inhibitors of Hh cholesterolysis using continuous light-to-dark FRET activity assay. [14][15][16] The FRET reporter construct, C-H-Y, has HhC flanked by cyan fluorescent protein (C) and yellow fluorescent protein (Y), providing the FRET donor and acceptor, respectively. FRET is measured as the ratio of emission of 540 nm / 460 nm after excitation at 400 nm.…”
Section: Resultsmentioning
confidence: 99%
“…There is a striking resemblance between the inhibitors described here and a family of noncovalent, allosteric activators of HhC, which we described previously (Figure 1, right). 14 The inhibitor/activator duality appears to be mediated by the same allosteric site on HhC, and stem from subtle differences in the structure of a heterocycle substituent on the effector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation